(untitled) (Third Sector Social Economic Review, 2023)
Intense competition and diverse customer expectations are raising concerns about organizational effectiveness. Workplace ostracism, which is on the rise, poses a significant threat to organizational effectiveness and needs to be addressed. Ostracism leads to negative workplace experiences and psychological distress, which can result in turnover intention and counterproductive work behavior. These behaviors cause significant losses, both directly and indirectly, in terms of results. This study aims to examine the impact of workplace ostracism on psychological distress, turnover intention, and counter-productive work behaviors, and how these consequences threaten organizational effectiveness. A theoretical and field study based on survey data was conducted, analyzing 329 surveys collected from two 5-star and three 3-star hotels operating in Rize. Regression analyses and hypothesis tests were performed to assess the data. According to the analysis results, workplace ostracism had a positive and significant effect on psychological distress (ß=227, p<0.05). Furthermore, the analyses that controlled for the effect of workplace ostracism showed that psychological distress had a significant and positive effect on counterproductive work behavior (ß=.695, p<0.05) and turnover intention (ß=.562, p<0.05). This study is expected to make significant contributions to the literature and help managers establish effective management practices in the workplace.